A combined CFD/visualization investigation of heat transfer behaviors during geyser boiling in two-phase closed thermosyphon. (June 2018) - Wang, Xiaoyuan; Wang, Yinfeng; Chen, Haijun; Zhu, Yuezhao
Highlights: Development of a phase-change model based on VOF method for a thermosyphon. The superheat needed for generating boiling is considered in modellings. Visualization experimental setup for an all-glass thermosyphon. Modelling results are compared and validated with experimental observations. The details of geyser boiling phenomenon are revealed. Abstract: In order to promote the understanding of geyser boiling in two-phase closed thermosyphon, a combined CFD/visualization investigation was carried out in this work. The widely used phase change model, i.e., Lee model, is improved by introducing the consideration of superheat to increase its prediction performance. CFD modellings of heat transfer behaviors during geyser boiling were performed using both the improved and original Lee model based on VOF method. These results were analyzed and compared to the visualized observations from experimental tests. The experimental results show that a periodic geyser boiling with the cycle time at 80–100 s occurs under the conditions that the flow rate of heating water is controlled at 400 mL/min (95 °C) and cooling water at 300 mL/min (30 °C). The corresponding modelling results in accordance with these experimental conditions suggest that the improved Lee model has a better prediction performance. The rapid slug bubble growth in expulsion period, and the surface evaporation and thermally natural convection in liquid pool during the incubation period are in good agreement with the experimental observations. In addition, the temperature and velocity contours during geyser boiling are comprehensively revealed by use of the improved Lee model.